Arthur babysits - Brown, Marc Tolon (Boston : Little, Brown and Company, 1992)
Arthur$1 (Bs experience babysitting for the terrible Tibble Twins is as challenging as he expected, but he finally gets control by telling them a spooky story.s
"An Arthur Adventure"--Cover.
Keywords: Aardvark -- Fiction; Babysitters -- Fiction